Cultural and Lexical Challenges: Analyzing Untranslatability in The French Subtitles of 'The Big 4' Film - Azzahra, Azzahra; Sunendar, Dadang; Amalia, Farida (Universitas Pendidikan Indonesia, 2024)
The present study aims to analyze the untranslatability occurred in the subtitle of The Big 4 (2022) movie from Indonesian as the source language (SL) to French as the target language (TL). The words or phrases in the subtitles taken from a movie streaming platform, Netflix, were analyzed using a qualitative method to analyze the type of untranslatability; whether it is a lexical or cultural untranslatability, factors that influence, and the techniques used by the translator to overcome the issues. The findings showed the existence of untranslatability in 107 instances, 24 of which were at the lexical level and 83 in cultural aspects. The translator utilized nine different translation techniques to address the untranslatability, including borrowing, naturalization, adaptation, particularisation, modulation, generalization, calque, established equivalence, and transposition. However, regardless of the phenomenon of untranslatability, the act of translation must continue. It is the duty of translators to be skillful in finding the equivalent expressions in the TL.